The Effects of Thymoquinone on Viability, and Anti-apoptotic Factors (BCL-XL, BCL-2, MCL-1) in Prostate Cancer (PC3) Cells: An In Vitro and Computer-Simulated Environment Study - Javad Saffari_Chaleshtori; Ehsan Heidari-Sureshjani; Fahimeh Moradi; Esfandiar Heidarian (Tabriz University of Medical Sciences, 2019)
Purpose: Since active plant ingredients can induce apoptosis in many tumors, in this study we evaluate the apoptotic effects of thymoquinone (TQ) on PC3 cells. Also, we predicted the interaction of TQ with BCL-XL, BCL-2, and MCL-1anti-apoptotic factors by computer-simulated environment. Methods: PC3 cells were treated with different concentrations of TQ (0- 80 µM) and IC50 was determined using 3-(4, 5-dimethylthiaztol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Apoptotic and cytotoxicity effects of TQ were analyzed using flowcytometry and comet assay, respectively. Changes in energy and the molecular interactions of TQ with BCL-XL, BCL-2 and MCL-1 anti-apoptotic factors were investigated using simulation. Results: IC50 value was 40 µM. TQ led to the destruction of the genome of PC3 cells and inducing apoptosis. Molecular dynamics (MD) revealed that the root mean-square deviation (RMSD), root mean square fluctuation (RMSF), radius of gyration (Rg), and the number of hydrogen and hydrophobic bonds between TQ and residues of BCL-2, BCL-XL and MCL-1were significantly (P<0.001) changed. TQ makes a more stable and stronger connection with BCL-XL compared to BCL-2 and MCL-1 and inhibits BCL-XL non-competitively. Conclusion: Our results demonstrated that TQ not only led to apoptosis, at least partly, due to reduction in the Coil, Turn, and Bend structure of BCL-XL but also caused a decrease in the Rg and RMSD value of BCL-XL, MCL-1, and BCL-2.